Psychosocial stress and cardiovascular diseases. Issue 957 (5th July 2005) - Vale, S
Abstract : Fifty five years after the first finding relating mood disturbances and cardiovascular diseases, there is still debate on the formation of a cogent conception embracing all the fragments of insight within the various aspects relating psychosocial stress to cardiovascular diseases. The clinical comorbidity is empirically evident, but there are ambiguous research results limiting the value of the proposed pathophysiological mechanisms. Psychosocial stress represents here any event that relates psychological phenomena to the social environment and to the associated pathophysiological changes. Stress denotes the external or environmental factors to which people are exposed, as well as the behavioural or biological reaction to it (response that some authors call "distress"). Cardiovascular diseases will be considered here only when being the consequence of chronic inflammatory disease of arteries (atherosclerosis).The question is: Are there pathophysiological reliable mechanisms relating psychosocial stress to the development of cardiovascular diseases?